About one decision of the quasiclassical kinetic equation - S O, Gladkov; S B, Bogdanova (International Journal of Engineering and Technology, 2018)
It has been proved that the solution of the quasi-classical kinetic equation for Bose and Fermi statistics can be represented in the general form, using the relaxation time approximation. The general solution found for the distribution function Â helps calculate any non â€“ equilibrium characteristics of metals, magnets, and dielectrics in any order of the perturbation theory according to the relaxation time .Â Â